2011
DOI: 10.1902/jop.2011.100736
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal Status of Patients With Hypophosphatemic Rickets: A Case Series

Abstract: The preliminary data from our study suggests that patients with hypophosphatemic rickets are more prone to periodontal bone loss than the general population and may require a more careful examination by dental care providers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 16 publications
2
23
0
Order By: Relevance
“…by exploring their overall periodontal status. Recently, a study has reported the periodontal condition of 10 adults with familial hypophosphatemic rickets (189). This study showed that 60% of the patients presented with periodontal bone lossa value much higher than those reported for periodontitis prevalence, of 3.6-7.3% (27,28)suggesting that patients with hypophosphatemic rickets have a tendency to experience an increase in periodontal bone loss and thus require more comprehensive examination by dental care providers.…”
Section: The Acidic Serine-and Aspartaterich Motif Peptide and Mineramentioning
confidence: 84%
“…by exploring their overall periodontal status. Recently, a study has reported the periodontal condition of 10 adults with familial hypophosphatemic rickets (189). This study showed that 60% of the patients presented with periodontal bone lossa value much higher than those reported for periodontitis prevalence, of 3.6-7.3% (27,28)suggesting that patients with hypophosphatemic rickets have a tendency to experience an increase in periodontal bone loss and thus require more comprehensive examination by dental care providers.…”
Section: The Acidic Serine-and Aspartaterich Motif Peptide and Mineramentioning
confidence: 84%
“…On dental radiographs, the pulp chambers of deciduous or permanent teeth are larger than usual with long pulp horns extending to the dentino-enamel junction 114,172 . XLH is not associated with increased susceptibility to caries 114,115,171 .…”
Section: Box 9 | Recommendations For Orthopaedic Management In Childrmentioning
confidence: 96%
“…Children and adult patients with XLH might present with spontaneous endodontic infections on apparently intact teeth 18,114,115,171 . Dental abscesses can develop on deciduous as well as on permanent teeth 16,171 . The endodontic infection might be asymptomatic for months or years or it might evolve…”
Section: Assessment Of Surgical Outcomesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is becoming clear that their periodontal health is also affected, especially in adults. Comparing the periodontal status of ten adults with familial HR with age-matched controls (73), it was observed that the prevalence of periodontitis was high in hypophosphatemic patients (60% vs 3.6% to 7.3% in controls). Our unpublished data on the periodontal status of more than 20 consecutive adult patients with HR revealed an increased prevalence and severity of periodontitis when compared with age-matched controls, despite a similar gingival inflammation (Fig.…”
Section: Dental and Periodontal Defectsmentioning
confidence: 99%